The Critical Study of Criminal System for Death Row Convicts Who Have Not Been Executed After the Enactment of National Criminal Code - Musdalifah, Dyajeng Ayu; Maskur, Muhammad Azil (JURNAL AKTA, 2025)
This article discusses the fate of death row inmates who have not been executed after the enactment of the National Criminal Code. The writing of this article uses a non-doctrinal legal method with a qualitative approach, this study uses primary and secondary data, and triangulation techniques. The focus of the research includes three problem formulations regarding the death row inmate punishment system after the enactment of the National Criminal Code, policies for death row inmates who have not been executed, and alternative policies that can be applied. The results of the study indicate that the National Criminal Code provides a 10-year probation period and the opportunity for sentence commutation for convicts who demonstrate good behavior. This policy reflects reforms in the Indonesian criminal system with an emphasis on rehabilitation and protection of human rights. The writing of this article is expected to contribute to the development of a more humane criminal law policy.